Customer Experience Dan Loyalitas Dalam Industri Kopi: Peran Mediasi Kepuasan - Safa, Safa; Teofilus, Teofilus; Yono, Hilda Yunita (Jambura Economic Education Journal, 2026)
This study examines Maleena Coffee Roasters' customer experience and loyalty relation with satisfaction. An online survey of 160 active consumers aged 18 or older who had made at least two transactions in May–July 2025 collected data. PLS-SEM analysis revealed a positive and significant impact of Customer Experience on Satisfaction (β=0.947; p0.001) and Loyalty (β=0.583; p0.001). Additionally, Satisfaction also had a positive effect on Loyalty (β = 0.350; p 0.001). Partial mediation is found, with an indirect effect of 0.331 (t=4,009; p0,001), indicating that satisfaction only partially transmits the influence of Customer Experience to Loyalty. Results suggest emotional, social, and sensory dimensions primarily drive loyalty, especially among Gen Z, while functional aspects are channeled more through satisfaction. Practical recommendations include optimizing customer experience through enhanced interactions, operational consistency, emotional connection, and behavioral analytics to foster both direct and satisfaction-based loyalty.